TPACK Research Trends in Indonesia: Contributions to Enhancing the Equivalency Education History Teacher Community - Leo Agung Sutimin; Sariyatun Sariyatun; Akhmad Arif Musadad; Tri Yuniyanto; Nur Fatah Abidin (Universitas Negeri Semarang, 2025)
Background: Technological Pedagogical Content Knowledge (TPACK) is a vital framework for integrating technology into education. In Indonesia, TPACK research has grown significantly, yet most studies focus on science and mathematics, leaving gaps in social studies, particularly history education. Additionally, its potential in supporting the equivalency education system, which serves non-formal learners, remains underexplored. Research Objectives: This study aims to analyze TPACK research trends in Indonesia (2019–2023), examine its contribution to the equivalency education history teacher community, and provide recommendations for integrating TPACK into history education. Research Method: Using bibliometric analysis, this study analyzed 1,208 documents from the Scopus database with the keyword